A practical evaluation of joint angle and delay estimation - Lindner, Thomas; Hafenecker, Sven; Hadaschik, Niels; Thielecke, Jörn (2015 International Conference on Indoor Positioning and Indoor Navigation (IPIN), 2015)
It has been proposed to jointly estimate the angles and delays of the paths in a multipath channel. It is interesting to investigate how this improves the precision of angle-of-arrival based localization systems. In this paper, we provide measurement results comparing the performance of ESPRIT-based algorithms for joint estimation to angle- and delay-only estimation in a single and a two-path scenario with different number of antennas and with different maximum length sequences as localization signal. It is shown that in the two-path scenario joint estimation provides improved precision compared to angle-only estimation. This holds true even when reducing the number of antennas used for joint estimation to half the number used for angle-only estimation. Within the results for joint estimation the longer sequences perform best. In the single-path scenario both methods perform similar to each other. There is no improvement in the precision of delay estimation in the two-path scenario.
Keywords: antenna arrays; direction-of-arrival estimation; multipath channels; time-of-arrival estimation; two-dimensional electron gas; ESPRIT-based algorithms; angle-of- arrival; angle-of-arrival based localization system precision improvement; angle-only estimation; delay-only estimation; joint angle-and-delay estimation; localization signal; multipath channel; time-of-arrival; Antenna arrays; Antenna measurements; Arrays; Delay estimation; Estimation; angle-of-arrival; joint angle and delay estimation; measurements; time-of-arrival

Influence of antenna array constellation on the accuracy of angle-of-arrival estimation in a multipath environment - Lindner, Thomas; Hadaschik, Niels; Patino-Studencki, Lucila; Thielecke, Jörn (WSA 2015; 19th International ITG Workshop on Smart Antennas, 2015)
Angle-of-arrival estimation is a widely used localisation method. However, multipath propagation leads to decreased performance. In this paper an expression for the Cramer- Rao lower bound for angle-of-arrival estimation with a known transmitted signal in a two path environment is derived. The influence of array structure on the achievable accuracy and the capability of signal separation is investigated. It is shown that sparse array structures provide a lower Cramer-Rao bound as long as uniqueness is preserved.

Optimal network topology for a locating system using RSSI-based direction finding - Nowak, Thorsten; Hartmann, Markus; Lindner, Thomas; Thielecke, Jörn (Indoor Positioning and Indoor Navigation (IPIN), 2015 International Conference on, 2015)
Location-awareness is one of the major challenges in wireless sensor networks (WSNs) today. Received signal strength indicator (RSSI)-based localization techniques are a promising approach to provide location information in WSNs utilizing low-cost hardware. In this paper, the performance of RSSI-based direction-of-arrival (DOA) is assessed. Therefore, the Cramér-Rao Lower Bound (CRLB) for direction estimation with RSSI measurements is derived in an analytical form. Furthermore, a position CRLB RSSI-based DOA estimates is presented. Since RSSI-based DOA is highly dependent on the direction of the received signal, and hence position estimates are, the network topology has a major impact on the feasible precision of the locating system. A methodology is shown to find the optimal WSN topology evaluating the position CRLB for RSSI-based DOA measurements.

Positioning with Angle-of-Arrival Estimation on Partially Coherent Arrays - Lindner, Thomas; Patino-Studencki, Lucila; Thielecke, Jörn (Smart SysTech 2016; European Conference on Smart Objects, Systems and Technologies, 2016)
Modern logistics requires precise tracking of objects. One way to achieve such tracking is via angle-of-arrival estimation with antenna arrays. Common approaches to high-resolution angle-of-arrival estimation require coherent reception of all antenna elements. However, it may be cheaper to cover the same aperture with just the outer antenna elements, while resolving ambiguity with two elements in half-wavelength spacing. We give bounds on the achievable accuracy with such an approach and provide measurements as proof-of-concept.

Sub 10μW wake-up-receiver based indoor/outdoor asset tracking system - Robert, Jörg; Lindner, Thomas; Milosiu, Heinrich (20th IEEE International Conference on Emerging Technologies and Factory Automation, ETFA 2015, 2015)
Localization and asset tracking are key components of the Internet of Things or the fourth industrial revolution called "Industry 4.0". Current systems using GPS signals cannot be used indoors. Alternative systems for indoor localization exist, but they cannot be battery power with tiny batteries over multiple years. To overcome these drawbacks we propose a new localization concept based on an ultra-low-power wake-up receiver. With a power consumption of less than 10μW the tags mounted on the assets are able to operate for multiple years using tiny coin type batteries. Nevertheless, out system concept can achieve an accuracy down to the sub-meter range. This goal is reached by means of beacon based field strength localization for the indoor environment, and angle-of-arrival estimation for the outdoor environment. An additional benefit of our wake-up receiver concept is the overall low latency.
Keywords: Accuracy; Batteries; Estimation; Logic gates; Radio transmitters; Receivers; Wireless communication

Time and Frequency Synchronization of a Wireless Sensor Network with Signals of Opportunity - Tröger, Hans-Martin; Patino-Studencki, Lucila; Hartmann, Markus; Lindner, Thomas; Heuberger, Albert; Thielecke, Jörn; Ereth, Stefan (Precise Time and Time Interval Systems and Applications 2014, 2014)
In wireless sensor networks used for positioning, the localization performance is generally closely connected to the time and frequency synchronization precision of the sensor nodes. In this paper we present an asset tracking system for indoor localization of goods, which is synchronized with the help of so-called Signals of Opportunity. Algorithms, originally developed for the decoding of DVB-T terrestrial broadcast signals, can be used for the synchronization of the receiver nodes. With a modified tracking loop, the frequency error between the local clock and the DVB-T transmitter clock can be continually estimated and corrected. Afterwards, a basic concept for time synchronization between the receiver nodes will be presented. Finally, the paper will conclude with an exemplary calculation of the time synchronization performance of the proposed concept.
UnivIS-Import:2017-12-18:Pub.2014.tech.IE.komele.timean